Detection of SARS-CoV-2 Post COVID-19 Vaccination in Health Workers in the COVID-19 Isolation Room - Kusumawati, R Lia; Hasibuan, Mirzan; Joli, Jelita Siregar (Talenta Publisher, 2023)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a type of virus that causes COVID-19 and is a global health problem that has a significant impact on the health of people around the world, including Indonesia. Health workers (nakes) as the frontline have a higher risk of exposure, especially health workers who work in the COVID-19 isolation room in hospitals. Health workers are the main priority for COVID-19 vaccine recipients, but post-vaccine infection does not rule out the possibility of COVID-19 infection due to health workers as health service providers who interact with other health workers or patients, or in patients who are not on transmission-based alert. Detection of SARS-CoV-2 should continue to be investigated and further action to reduce the risk of infection to health workers. This community service activity was carried out to help facilitate health workers during the post-vaccination SARS-CoV-2 examination (I, II and booster III). Of the 73 health workers, nurses are the health workers who mostly work in the COVID-19 isolation room 56 (77%), doctors 11 (15%), midwives 4 (5%) and laboratory assistants 2 (3%). Based on the results of the COVID-19 examination using the RT-PCR method from the nasopharyngeal swab sample, it showed that there were 19 health workers who were infected with COVID-19 before vaccination, namely 1 (1.3%) doctors and 18 (24.6%) nurses. The decrease in infection with health workers decreased after health workers received the first vaccination, where only 1 (1.3%) doctors and 2 (2.7) nurses were reinfected, the increase in the number of health workers infected with SARS-CoV-2 after vaccination II was 3 (4.1%) doctors, 12 (16.4%) and 2 (2.7%) midwives. The results of the detection of SARS-CoV-2 in 73 health workers who had been vaccinated with booster III (moderna) did not find any SARS-CoV-2 infection, indicating that vaccine III increases self-protection against SARS-CoV-2 infection.